Anti-Inflammatory Activity Test of Mangrove Root (Sonneratia alba) Ethanol Extract Gel Preparation in Carragenan-Induced White Rats (Rattus norvegicus) - Alfared S. Simanjuntak; Jeane Mongi; Wilmar Maarisit; Yessie K. Lengkey; Christel N. Sambou; Douglas N. Pareta (FMIPA UKIT, 2025)
Nature provides various compounds that can provide anti-inflammatory activity, one of which is the compound contained in mangrove roots (Sonneratia alba). In these plants, especially in the roots, there are secondary metabolite compounds such as alkaloids, flavonoids, tannins, triterpenoids and from various reported research results, flavonoids have anti-inflammatory properties. The medicinal preparation that the researchers want to make is a gel preparation that is used for topical treatment therapy. The research was carried out with 15 rats into 5 test groups. Positive control group: given Diclofenac Sodium gel (Voltadex) 20 g (1%), negative control group: given gel without ethanol extract, 2.5% concentration group: given 2.5% ethanol extract gel, 5% concentration group: given 5% ethanol extract gel, 10% concentration group: 10% ethanol extract gel was given. The data was analyzed descriptively and presented in the form of tables and graphs. The research results showed that the Sonneratia alba ethanol extract gel preparation had anti-inflammatory activity. The research results show that the ethanol extract of Sonneratia alba mangrove roots can be used as a gel preparation and in in vivo testing the gel preparation of Sonneratia alba mangrove root ethanol extract has anti-inflammatory activity. The control group of Sonneratia alba mangrove root ethanol extract gel preparations of concentrations of 2.5%, 5% and 10% had a swelling inhibition percentage, which means that Sonneratia alba mangrove root ethanol extract gel preparations of 2.5%, 5% and 10% concentration had anti-inflammatory activity.